Detection and genotyping of HPV in women with indeterminate cytology and low-grade squamous intraepithelial lesions - Francisca A. Queiroz; Danielle A. P. Rocha; Roberto Alexandre A. B. Filho; Cristina Maria B. Santos (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: The human papillomavirus (HPV) is the main risk factor related to cervical cancer, the third most frequent type of cancer in Brazilian women. Early identification of high-risk HPV types in the normal cervix, or cervix with premalignant lesions may help prevent the progression of these lesions to cancer. Objective: This study aimed to detect and genotype HPV in women with low-grade intraepithelial lesion (LSIL) and atypical squamous cells of undetermined significance (ASC-US). Methods: Patients were selected from files of the cytology laboratory of Fundação Alfredo da Mata (FUAM), between January 2009 and July 2011, for cytological reassessment and HPV molecular detection with genotyping. Results: Out of the100 eligible patients, 70% (70/100) participated in the study; initially, 34 of them had ASC-US and 36 had LSIL. After cytological reassessment, eight (11.4%) patients showed normal cytology; 33 (47.2%), inflammatory lesions; 22 (31.4%), ASCUS; six (8.6%), LSIL; and one (1.4%), high-grade squamous intraepithelial lesions (HSIL). HPV was detected in 28.6% (20/70) of the samples. Out of the 20 HPV-positive patients, one had normal cytology, six showed inflammatory cytology, 10 showed ASCUS, two had LSIL and one, HSIL. After genotyping, the HPV types identified were: 6, 16, 58, 61, 70, 83, 84 and 85. The most prevalent HPV type was the 58. Conclusion: The presence of high-risk HPV in women with old cervical lesions, whether they have evolved or not, indicates the need to improve patient monitoring and surveillance.